Liquefaction disaster mitigation on railway corridors in Padang City, West Sumatra. Issue 1 (April 2021) - Adji, B M; Istijono, B; Hakam, A; Andriani, Satriawan; Anshari, M
Abstract: Earthquake-induced liquefaction, which turns the soil to liquid from solid, can cause substantial lateral movement to the ground surface. It has detected the potential liquefaction due to earthquakes in WestWest Sumatra is very high. The most problems due to liquefaction are loss of stability and significant settlements. For particular infrastructure such as railway, liquefaction has a considerable influence on the railway embankments. Then, it needs to be investigated whether the railway corridors are built in areas with a high potential of liquefaction. The analysis method used in this research is by comparing railway corridors against the Map of West Sumatra liquefaction potential. This study presents the most railway corridors in West Sumatra that were built in areas with having the liquefaction potential. For the corridors which may be potentially destroyed by liquefaction, special treatment must be applied to them.